PENGARUH PENDEKATAN DEEP LEARNING TERHADAP KEMAMPUAN BERPIKIR TINGKAT TINGGI (HIGHER ORDER THINKING SKILL) SISWA KELAS V DI SD NEGERI 2 DANGIN PURI DENPASAR - Dewa Ayu Suargiri; Anak Agung Ngurah Budiadnyana; I Made Putra Aryana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Higher Order Thinking Skills (HOTS) are among the essential competencies that need to be developed in 21st-century learning. However, elementary school students’ HOTS are still relatively low because learning activities tend to be teacher-centered and focus more on memorization. The Deep Learning approach is considered capable of encouraging meaningful, contextual, and reflective learning processes that can improve students’ higher-order thinking skills. This study aimed to determine the effect of the Deep Learning approach on the higherorder thinking skills of fifth-grade students at SD Negeri 2 Dangin Puri. The theories used in this study were constructivist theory and Deep Learning learning theory. This study employed a quantitative approach with a Quasi Experimental Design using a Nonequivalent Control Group Design. The population consisted of 54 fifth-grade students of SD Negeri 2 Dangin Puri using a saturated sampling technique. Data were collected through observation, interviews, and tests. The data were analyzed using descriptive and inferential statistics. The results showed that the implementation of the Deep Learning approach had a significant effect on students’ Higher Order Thinking Skills (HOTS). Based on the Independent Sample t-Test, the obtained significance value of Sig. (2-tailed) < 0.001. Since the significance value was lower than 0.05, H₀ was rejected and H₁ was accepted. This result indicated a significant difference between the experimental and control groups. Therefore, it can be concluded that the Deep Learning approach significantly affected the improvement of fifth-grade students’ higher-order thinking skills at SD Negeri 2 Dangin Puri.